Технология создания легированных бором слоев на алмазе - Zyablyuk, K. N.; Mityagin, A. Yu.; Talipov, N. H.; Chucheva, G. V.; Duhnovskii, M. P.; Khmel’nitskii, R. A. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
The authors investigated natural type IIa diamond crystals and CVD diamond films. The article presents electrophysical parameters of the structures obtained in different modes of ion implantation of boron into the crystal with further annealing. Parameters of the crystals with a high nitrogen impurity density indicate that they can be used for the manufacture of microwave field-effect transistors operating at room temperature. CVD diamond films doped with boron during the growth process also have the required for MOSFET manufacture carrier mobility. However, due to the high activation energy of boron, the required channel conductivity is achieved at high operating temperatures.